2019
DOI: 10.1007/s11916-019-0750-8
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Integrative Medicine for Episodic Migraine: an Update of Evidence from the Last 3 Years

Abstract: Objective-The purpose of this review is to evaluate evidence from the last three years on complementary and integrative medicine treatment options for episodic migraine.Methods-Using Pubmed, Embase, and Cochrane databases, research published from 2015-2018 evaluating themodalities of mind/body therapies, supplements, and manual therapies for treatment of migraine were assessed.Results-Although many studies had major methodological challenges that limit interpretation, several studies reported decreased headach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 67 publications
0
58
0
Order By: Relevance
“…Indeed, existing knowledge shows that magnesium, vitamin B2, feverfew and coenzyme Q10 are helpful in migraine prophylaxis with minimal safety issues, as these nutrients might be able to target some of the processes involved in migraine pathogenesis. 28 Speci cally, magnesium blocks glutamate receptors, modulates ATP production and glucose metabolism and as such high dose supplementation is able to decrease glutamate-activated cortical spreading depression. Likewise, high dose supplementation with vitamin B2 and coenzyme Q10 may augment activity of mitochondrial complexes to prevent mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, existing knowledge shows that magnesium, vitamin B2, feverfew and coenzyme Q10 are helpful in migraine prophylaxis with minimal safety issues, as these nutrients might be able to target some of the processes involved in migraine pathogenesis. 28 Speci cally, magnesium blocks glutamate receptors, modulates ATP production and glucose metabolism and as such high dose supplementation is able to decrease glutamate-activated cortical spreading depression. Likewise, high dose supplementation with vitamin B2 and coenzyme Q10 may augment activity of mitochondrial complexes to prevent mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It was shrouded in a belief that the piercing acts as a gateway for only knowledge to pass through the ear [2]. The piercing gained mainstream popularity in the following years and has been subsequently used for migraine as an alternate treatment by some patients with anecdotal patient reports online suggesting an improvement in symptoms [3]. This case illustrates a current common health-related practice in the community, the awareness of which could help the provider to manage this condition better.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, individuals with migraine often prefer to avoid daily medication and instead seek non‐pharmacologic options, including complementary and integrative health (CIH) therapies . There is some evidence that these therapies may be helpful for patients with episodic migraine …”
Section: Introductionmentioning
confidence: 99%
“…9,10 There is some evidence that these therapies may be helpful for patients with episodic migraine. 11 While many patients reported using CIH therapies, others did not know what CIH therapies are available or how to access them. In addition, some patients reported that they had tried different combinations of complementary therapies, often without success or evidence of efficacy.…”
Section: Introductionmentioning
confidence: 99%